ISOLATION OF ACTIVE COMPOUND FROM ZINGIBER PURPUREUM ROXB. USING BIOASSAY GUIDED FRACTINATION METHOD FOR WIDR COLON ADENOCARCINOMA CELL LINE - rollando rollando (Journal of Global Pharma Technology, 2018)
Zingiber purpureum Roxb. was a plant that has the potential to be developed as a chemotherapy agent. Bioassay guided fractination aims to examine the anticancer activity of n-hexane, ethyl acetate, and methanol fractions from ethanolic extract of bangle plant rhizome to colon cancer cell type WiDr and Vero cells. The apoptotic test and modulating cell cycle were observed by flow cytometry method. Isolation process of the most active fraction. The pure isolates obtained were identified by structures with structural elucidation using ultraviolet, 1D-NMR, 2D-NMR and liquid chromatography-mass spectrometer. Obtained 2,3-dihydro-5-hydroxy-7-methoxy-2-phenylchromen-4-one compound of ethyl acetate fraction number 21. With a value of CC50 to a WiDr cell of 11.24 ± 3.44 μg/mL and 342.22 ± 4.98 μg/mL to Vero cells.